Cystic echinococcosis in slaughtered cattle and sheep from North Macedonia - Ljubica Rashikj; Aleksandar Cvetkovikj; Martin Nikolovski; Iskra Cvetkovikj; Jovana Stefanovska (Macedonian Veterinary Review, 2022)
Cystic echinococcosis is a cosmopolitan zoonotic infection, commonly seen in areas where livestock and dogs are kept together. The objective of this study was to investigate the prevalence of echinococcosis in slaughtered cattle and sheep in North Macedonia and to evaluate the location and fertility/sterility rates of the cysts. A total of 302 slaughtered animals were examined with visual inspection, palpation, and incision of the internal organs in order to detect cysts. Microscopic examination was carried out to determine the presence of protoscoleces. The overall prevalence of echinococcosis in slaughtered cattle and sheep was 60%. The presence of cysts increased with age in cattle. In both cattle and sheep, the most common affected organs were the liver and lungs infected with more than one cyst. The findings showed higher fertility rate in sheep which confirmed their role as the most important intermediate host. This study shows that North Macedonia is an endemic region, and serious control strategies should be implemented, with special emphasis on safety disposal of infected organs and anthelmintic treatment of the dogs.